Faculty Reopening Committee: A Study of Chair and Faculty Collaboration - Jeffrey Ward (Academic Chairpersons Conference Proceedings, 2022)
The presenter will share experiences with a self-selected group of volunteer faculty to form a Reopening Committee, offering conclusions not only about the committee but also about also how it more broadly illustrates principles of faculty governance and collegial relationships among faculty and between the faculty and the department head.
Keywords: Leadership; Management; COVID; Pedagogy; Facilities